Effectiveness of Physical Activity Intervention on ADHD Symptoms: A Systematic Review and Meta-Analysis - Xie, Yongtao; Gao, Xuping; Song, Yiling; Zhu, Xiaotong; Chen, Mengge; Yang, Li; Ren, Yuanchun (Frontiers in Psychiatry, 2021)
Objective: To assess the effectiveness of physical activity (PA) intervention on attention-deficit/hyperactivity disorder (ADHD)-related symptoms. Method: Studies that investigated PA intervention for ADHD-related symptoms were identified through searching PubMed, Web of Science, Cochrane Library, and Embase databases from inception through June 2021. Standardized mean difference (SMD) with 95% confidence interval (CI) was used to assess the effectiveness of PA intervention on improving ADHD-related symptoms. The meta-analyses were conducted using fixed-effect or random-effect models according to the heterogeneity of the studies. Results: Nine before–after studies (232 participants) and 14 two-group control studies (162 participants/141 controls) were included in this meta-analysis. Combined results for before–after studies indicated significant improvements on all studied ADHD-related symptoms (inattention: SMD = 0.604, 95% CI: 0.374–0.834, p < 0.001; hyperactivity/impulsivity: SMD = 0.676, 95% CI: 0.401–0.950, p < 0.001; emotional problems: SMD = 0.416, 95% CI: 0.283–0.549, p < 0.001; behavioral problems: SMD = 0.347, 95% CI: 0.202–0.492, p < 0.001). Meta-analyses for two-group control studies further confirmed that PA intervention significantly improved the inattentive symptom (SMD = 0.715, 95% CI: 0.105, 1.325, p = 0.022). Subgroup analyses suggested significant beneficial effect on inattention symptoms in children. Moreover, closed motor skills were beneficial for hyperactive/impulsive problems (SMD = 0.671, p < 0.001), while open motor skills were beneficial for attention problems (SMD = 0.455, p = 0.049). When excluding studies with combined medication, the studies in unmedicated participants in before–after studies still showed significant results in all studied ADHD-related symptoms as in the overall analysis. Given the limited sample size, the best frequency and intensity of PA intervention need further investigation. Conclusion: Our results suggested that PA intervention could possibly improve ADHD-related symptoms, especially inattention symptoms. Closed-skill and open-skill activities could be beneficial for hyperactivity/impulsivity and inattention symptoms, respectively. Further high-quality randomized clinical trials with large sample size are needed.